NET1 is a critical regulator of spindle assembly and actin dynamics in mouse oocytes - Shiwei Wang; Xuan Wu; Mengmeng Zhang; Siyu Chang; Yajun Guo; Shuang Song; Shizhen Dai; Keliang Wu; Shenming Zeng (BMC, 2024)
Abstract Background Neuroepithelial transforming gene 1 (NET1) is a RhoA subfamily guanine nucleotide exchange factor that governs a wide array of biological processes. However, its roles in meiotic oocyte remain unclear. We herein demonstrated that the NET1-HACE1-RAC1 pathway mediates meiotic defects in the progression of oocyte maturation. Methods NET1 was reduced using a specific small interfering RNA in mouse oocytes. Spindle assembly, chromosomal alignment, the actin cap, and chromosomal spreads were visualized by immunostaining and analyzed under confocal microscopy. We also applied mass spectroscopy, and western blot analysis for this investigation. Results Our results revealed that NET1 was localized to the nucleus at the GV stage, and that after GVBD, NET1 was localized to the cytoplasm and predominantly distributed around the chromosomes, commensurate with meiotic progression. NET1 resided in the cytoplasm and significantly accumulated on the spindle at the MI and MII stages. Mouse oocytes depleted of Net1 exhibited aberrant first polar body extrusion and asymmetric division defects. We also determined that Net1 depletion resulted in reduced RAC1 protein expression in mouse oocytes, and that NET1 protected RAC1 from degradation by HACE1, and it was essential for actin dynamics and meiotic spindle formation. Importantly, exogenous RAC1 expression in Net1-depleted oocytes significantly rescued these defects. Conclusions Our results suggest that NET1 exhibits multiple roles in spindle stability and actin dynamics during mouse oocyte meiosis.